Multiple indole glucosinolates and myrosinases defend Arabidopsis against Tetranychus urticae herbivory. Issue 1 (19th June 2021) - Widemann, Emilie; Bruinsma, Kristie; Walshe-Roussel, Brendan; Rioja, Cristina; Arbona, Vicent; Saha, Repon Kumer; Letwin, David; Zhurov, Vladimir; Gómez-Cadenas, Aurelio; Bernards, Mark A.; Grbić, Miodrag; Grbić, Vojislava
Abstract: Arabidopsis ( Arabidopsis thaliana ) defenses against herbivores are regulated by the jasmonate (JA) hormonal signaling pathway, which leads to the production of a plethora of defense compounds. Arabidopsis defense compounds include tryptophan-derived metabolites, which limit Arabidopsis infestation by the generalist herbivore two-spotted spider mite, Tetranychus urticae . However, the phytochemicals responsible for Arabidopsis protection against T. urticae are unknown. Here, we used Arabidopsis mutants disrupted in the synthesis of tryptophan-derived secondary metabolites to identify phytochemicals involved in the defense against T. urticae . We show that of the three tryptophan-dependent pathways found in Arabidopsis, the indole glucosinolate (IG) pathway is necessary and sufficient to assure tryptophan-mediated defense against T. urticae . We demonstrate that all three IGs can limit T. urticae herbivory, but that they must be processed by myrosinases to hinder T. urticae oviposition. Putative IG breakdown products were detected in mite-infested leaves, suggesting in planta processing by myrosinases. Finally, we demonstrate that besides IGs, there are additional JA-regulated defenses that control T. urticae herbivory. Together, our results reveal the complexity of Arabidopsis defenses against T. urticae that rely on multiple IGs, specific myrosinases, and additional JA-dependent defenses. Abstract : Three IGs and specific myrosinases help protect Arabidopsis thaliana against herbivory by the two-spotted spider mite T. urticae.